2021
DOI: 10.3390/cimb43030110
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of DNA Methylation and Alternative Splicing of Genes in Skeletal Muscle of Obese Rabbits

Abstract: DNA methylation and the alternative splicing of precursor messenger RNAs (pre-mRNAs) are two important genetic modification mechanisms. However, both are currently uncharacterized in the muscle metabolism of rabbits. Thus, we constructed the Tianfu black rabbit obesity model (obese rabbits fed with a 10% high-fat diet and control rabbits from 35 days to 70 days) and collected the skeletal muscle samples from the two groups for Genome methylation sequencing and RNA sequencing. DNA methylation data showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…, Titin and Pgc1α ) and increasing the risk of deficiency in skeletal muscle mass and amyosthenia. 8,45,46 Consequently, enhancing the DNA demethylation capacity of skeletal muscles can help to restore the skeletal muscle function. The levels of 5hmC and 5fC, which are intermediate products obtained by the repeated oxidation of 5mC by TETs, correspond to the degree of demethylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Titin and Pgc1α ) and increasing the risk of deficiency in skeletal muscle mass and amyosthenia. 8,45,46 Consequently, enhancing the DNA demethylation capacity of skeletal muscles can help to restore the skeletal muscle function. The levels of 5hmC and 5fC, which are intermediate products obtained by the repeated oxidation of 5mC by TETs, correspond to the degree of demethylation.…”
Section: Discussionmentioning
confidence: 99%
“…15,44,45 Clinical and experimental data suggest that a HFD can lead to skeletal muscle hypermethylation, in turn suppressing the expression of numerous genes essential for skeletal muscle growth (e.g., Titin and Pgc1α) and increasing the risk of deficiency in skeletal muscle mass and amyosthenia. 8,45,46 Consequently, enhancing the DNA demethylation capacity of skeletal muscles can help to restore the skeletal muscle function. The levels of 5hmC and 5fC, which are intermediate products obtained by the repeated oxidation of 5mC by TETs, correspond to the degree of demethylation.…”
Section: Food and Function Papermentioning
confidence: 99%
“…In a cattle study, the ANKRD23-202 mRNA isoform, which is a splice form of the ANKRD, was defined as a DEI between the tough group and the tender group [49]. The result of a rabbit study suggested that ANKRD23 methylated in promoter and gene body regions is associated with exon skipping alternative splicing in the skeletal muscle [51]. Previous results suggest that CTCF could regulate alternative splicing by controlling DNA methylation [52][53][54].…”
Section: Ctcf Might Regulate Alternative Splicing In Sheep Musclementioning
confidence: 99%